1931 Tenn. Priv. Acts 1089, vol. 2, An Act to Be Entitled, "An Act to Incorporate the City of Murfreesboro in Rutherford County, Tennessee . . . ," ch. 429, art. 3, § 4, pt. 46. - (:unkn) unknown (My University, 1931)
To regulate, restrain, and prevent the carrying on of manufactories dangerous in causing or producing fires; and to regulate and suppress the sale of firearms, and to prevent and suppress the selling, carrying, using or firing of pistols, rifles, guns, bowie knives, dirks, firearms, or other deadly weapons.
Keywords: CARRY; TRANSFER